PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN ATMOSFER RESTORAN TERHADAP MINAT BELI ULANG KONSUMEN (Kajian terhadap sebuah restoran x di Makassar) - Justin Kosli; Victor Kurniawan Yuwono; Moses Soediro (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
The increase in the number of cafes and restaurants in Makassar since 2019 has been significant. However, the impact of this increase is the intensification of competition among business operators. This competition has led cafes and restaurants to compete in order to stay open or operational. A negative consequence of the proliferation of cafes and restaurants is the tendency of consumers to only follow trends on social media. This results in an initial surge in visits during the first 3 to 6 months after the opening of a cafe or restaurant, followed by a significant decline in sales. The decrease in purchasing interest is also influenced by negative comments from dissatisfied customers, which ultimately damage the reputation of the cafe or restaurant. Therefore, strategies are needed to help cafes and restaurants sustain their operations and maintain customer interest. One example is Restaurant X, a restaurant in Makassar that has been operating since 2017. A survey was conducted with 30 customers, and the most important factors identified were brand image, product quality, and restaurant ambiance. These variables will be further tested for their impact on customers repurchase intentions using quantitative methods. The results of this study indicate that both brand image and product quality have a positive and significant impact on customers repurchase intentions. However, the ambiance of the restaurant does not have a significant positive effect on customers repurchase intentions.